The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10586-015-0426-z
|View full text |Cite
|
Sign up to set email alerts
|

CRFs based parallel biomedical named entity recognition algorithm employing MapReduce framework

Abstract: As the rapid growth of the biomedical literature, the model training time in biomedical named entity recognition increases sharply when dealing with large-scale training samples. How to increase the efficiency of named entity recognition in biomedical big data becomes one of the key problems in biomedical text mining. For the purposes of improving the recognition performance and reducing the training time, this paper proposes an optimization method for two-phase recognition using conditional random fields. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the first phase boundaries of entities are identified while in the second phase semantic labeling is performed to label the detected entities. A CRF based system has been proposed by (Tang et al, 2015), where in the first step boundaries of NEs are identified and in the second step appropriate labels are assigned. (Grouin, 2014) performed experiments on the i2b2/VA-2010 challenge dataset to detect bacteria and biotopes names.…”
Section: Related Workmentioning
confidence: 99%
“…In the first phase boundaries of entities are identified while in the second phase semantic labeling is performed to label the detected entities. A CRF based system has been proposed by (Tang et al, 2015), where in the first step boundaries of NEs are identified and in the second step appropriate labels are assigned. (Grouin, 2014) performed experiments on the i2b2/VA-2010 challenge dataset to detect bacteria and biotopes names.…”
Section: Related Workmentioning
confidence: 99%
“…For most deep neural networks-based NER methods, chain CRF [10] acts as the tag decoder. However, as an alternative, recurrent neural networks (RNNs) can be also used for decoding tags of sequences [11][12][13].…”
Section: Related Workmentioning
confidence: 99%
“…It is worth mentioning that given the large amount of biomedical documents and texts that need to be processed by NER tools, several researchers have looked at optimizing the parallel capabilities of these tools. The work by Tang et al [ 53 ] and Li et al [ 54 ] are two notable recent work in this respect. These two works contend that given the sequential nature of CRF models, their parallelization is not trivial.…”
Section: Entity-specific Biomedical Annotation Toolsmentioning
confidence: 99%